Shifting shadows - Hunter, Erin (Hunter, Erin. Bravelands, 2020)
The false leader Stinger has died, but the animals of the Bravelands still find no peace. No Great Parent has taken on the leadership, and the imbalance threatens all. Thorn struggles with a burden, Sky longs for the Great Spirit, and Fearless blames himself when an ally is put into grave danger.